Effect of HNTs addition in the injection moulded thermoplastic polyurethane matrix on the mechanical and thermal properties - Gaaz, Tayser Sumer; Abu Bakar Sulong,; Abdul Amir H. Kadhum, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The additions of nanofillers are able to enhance the mechanical properties of neat polymer matrix. There were few researchers reported on the mechanical properties of halloysite nanotubes reinforced thermoplastic polyurethane (HNTs-TPU) nanocomposites formed through casting and compression moulding. However, fewer researchers also reported study on HNTs-TPU formed through injection molding. The main objective of this paper was to study the effect of HNTs addition of TPU matrix on mechanical and physical properties. HNTs were mixed in TPU matrix using a brabender mixer with concentration ranging from 0.5 to 7 wt. % HNT loading (at specific mixing speed, mixing time and mixing temperature). Injection moulding was carried out to form tensile bar shaped specimens with specific moulding parameters (injection temperature, injection time and injection pressure). Increment around 35% of tensile strength of the specimen was found at 1 wt. % HNT loading concentration which exhibited the value of 24.3 MPa, compared to neat TPU; the best mixing. The Young’s modulus was increased with increasing HNTs loading. The elongation decreased with increasing HNTs loading. The FESEM results showed that HNTs were dispersed in TPU matrix. The TGA results showed that the addition of 1 wt. % HNTs enhanced the thermal properties. It can be concluded that HNTs-TPU has improved tensile and physical properties compared with neat TPU due to the addition of nanofiller.